Assessment of balance in sport: Science and reality - Zemkova, E. (Serbian Journal of Sports Sciences, 2011)
This paper deals with traditional and contemporary techniques for assessing balance, and the ways in which sport scientists can bridge the gap between balance research and practice. For many years our research has been centered on issues dealing with sport-specific balance testing. Particularly, static and dynamic posturography and recently task-oriented balance tests have also been used to assess postural stability under sport-specific conditions. Though such assessment has shown sufficient reliability of repeated measurements, there has been a problematic discrimination of athletes with a higher level of balance capabilities. Hence, alternative methods, such as stabilogram-diffusion analysis, have been used to investigate the dynamic nature of postural sway. Different approaches have provided us with experience in the role balance plays in sport performance. This has also contributed to a better understanding of physiological mechanisms of post-exercise balance impairment and served as a basis for the design of goal-specific balance training programs. Findings gained in the field of sport can be explored in clinical medicine and rehabilitation.